Análisis prospectivo de la efectividad del cannabidiol en la recuperación post ejercicio : Revisión integradora y agenda de investigación futura. - Villalobos González, Carmen Elena (C.E. Villalobos G., 2023)
Fundamental motor skills are the basis for participation in more advanced lifetime activities. Whereas considerable research has been reported on motor behavior of children, much less is known about performance in later years, especially adulthood. Therefore, the aim of this study was to examine age and gender differences on fundamental motor skills (FMS) ability across three age groups: children (M = 9.37 yr., SD = 1.26), adolescents (M = 14.80 yr., SD = 2.04) and young-adults (M = 19.88 yr., SD = 2.72). Participants (n = 114) were assessed on five locomotor skills (run, gallop, slide, hop, and distance jump) and five object control skills (bounce, catch, overhand throw, strike and kick) using the Test for Fundamental Motor Skills, which is a process-oriented instrument. ANOVA results comparing gender and group revealed no significant interactions. Moreover, main effects for group were found for three individual skills: galloping - adolescents and young-adults performed better than children (p < .01)-, throwing -children and adolescents performed better than young-adults (p < .01) -, and kicking -young-adults performed better than children and adolescents (p < .05)-.